A Case of Wolfram Syndrome Presenting with Restlessness - Mowla, Syed Ghulam Mogni; Miah, Md Titu; Rahman, Ashraf Ur; Shonchoi, Shamsuddoha Sarker; Alam, Muhammad Nazmul; Salim, Mohammad (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Wolfram Syndrome ( DIDMOAD) is a rare genetic disorder presenting with Diabetes Insipidus, Diabetes Mellitus, Optic Atrophy, Deafness and some other neurological , reproductive , hormonal, urological and psychic problems. About 200 cases have been reported so far. Here we present a 25 years old Bangladeshi male having early onset Diabetes Mellitus, optic atrophy, deafness and many other features consistent with Wolfram Syndrome. We examined the patient thoroughly and did necessary investigations to confirm our diagnosis. As there is no cure of this disorder, we gave symptomatic and supportive treatment to the patient to make his life easier. Although the outcome is unrewarding , such patients will be kept in regular follow up for early detection of new complications and possible solutions. J Bangladesh Coll Phys Surg 2016; 34(1): 42-44